TYPE D PERSONALITY TRAIT AND RESILIENCE AMONG MEDICAL STUDENTS: A SURVEY AT A PRIVATE UNIVERSITY IN ISLAMABAD (Contemporary Journal of Social Science Review, 2025)
Objectives: 1)To determine frequency of Type D Personality in undergraduate medical students, 2) To evaluate the Resilience levels in undergraduate medical students, 3) To determine any association between Type D Personality and Resilience.Design:  Cross-sectional studyPlace & duration of study: The study was conducted at an undergraduate medical institution in Islamabad Pakistan, from March 2022 to October 2022. Materials and Methods: A total of 385 undergraduate medical students were recruited through non-probability convenience sampling techniques, to determine Type D Personality and level of resilience, through questionnaires which included the DS14 and BRS-6 scales. Informed consent of the respondents was taken. Using SPSS 21, Descriptive Statistics were applied and results were displayed as frequencies and tables. Inferential statistics like t test and Chi squared test were applied, and associations of Type D personality and Resilience levels were calculated using Pearson’s Correlation.Results:  Out of all the respondents 125 were males (32.5%) and 260 were female (67.5%)  Frequency of Type D personality was calculated to be 211 ( 54.8%). Frequencies for Resilience were 141 (36.6%), 223 (57.9%), and 21 (5.5%) for Low, Normal and High Resilience categories respectively. A negative correlation was found between both subsets of Type D Personality and Resilience, with r= -0.380 (sig at 0.0001) between Negative Affectivity and Resilience scores, and r=-0.193 (sig at 0.0001) between Social Inhibition and Resilience scores, using Pearson’s Correlation.Conclusion: There is an alarmingly high frequency of Type D personality in undergraduate students at the university. More than a third of the respondents had Low Resilience. Furthermore, there is negative correlation between Type D Personality, and levels of Resilience, i.e. students with Type D personality have been found to have lower levels of Resilience.